2014
DOI: 10.1007/s11356-014-3022-5
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and fate of acrylamide in water-recycling systems and sludge in aggregate industries

Abstract: Acrylamide is a hazardous substance having irritant and toxic properties as well as carcinogen, mutagen, and impaired fertility possible effects. Acrylamide might be found in the environment as a consequence of the use of polyacrylamides (PAMs) widely added as a flocculant for water treatment. Acrylamide is a monomer used to produce polyacrylamide (PAM) polymers. This reaction of polymerization can be incomplete, and acrylamide molecules can be present as traces in the commercial polymer. Thus, the use of PAMs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The high percentage of adsorption found at low AMD concentrations could be attributed to the analytical uncertainty that should be high at this concentration level. Our results explain why no accumulation of AMD can occur in sludge samples and confirm the findings of Junqua et al (2014). …”
Section: Results Fromsupporting
confidence: 88%
See 3 more Smart Citations
“…The high percentage of adsorption found at low AMD concentrations could be attributed to the analytical uncertainty that should be high at this concentration level. Our results explain why no accumulation of AMD can occur in sludge samples and confirm the findings of Junqua et al (2014). …”
Section: Results Fromsupporting
confidence: 88%
“…Backe et al (2014) detected acrylamide concentrations of 0.28 μg/L in waters from the holding pond of sand and gravel mines. Junqua et al (2014) and Backe et al (2014) both found very low concentrations of AMD in water-reused process. Nevertheless, Junqua et al (2014) pointed out the relevance to study AMD mobilization and runoff as well as its degradation in water and sludge.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The low affinity of AMD to soil and clay minerals in particular is likely due to its high hydrosolubility and small size (Sojka et al 2007). Analysis of a lake water, directly connected to groundwaters, suggest a likely transfer of AMD due to its infiltration in soils (Junqua et al 2013). The half-life of acrylamide monomer in rivers ranges from weeks to months (Brown et al 1980).…”
Section: Transfer Of Amdmentioning
confidence: 99%